2015
DOI: 10.1016/j.jtrangeo.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Methods for deriving and calibrating privacy-preserving heat maps from mobile sports tracking application data

Abstract: Utilization of movement data from mobile sports tracking applications is affected by its inherent biases and sensitivity, which need to be understood when developing value-added services for, e.g., application users and city planners. We have developed a method for generating a privacy-preserving heat map with user diversity (ppDIV), in which the density of trajectories, as well as the diversity of users, is taken into account, thus preventing the bias effects caused by participation inequality. The method is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 39 publications
0
28
0
Order By: Relevance
“…Rossi et al [57] demonstrated how sensitive GPS trajectories are in terms of privacy, while de Montjoye et al [58] proved that even coarsened movement data provide information about individuals. Oksanen et al [59], therefore, proposed a method to preserve privacy in mobility hotspot maps.…”
Section: Data Availability Accessibility and Privacy Concernsmentioning
confidence: 99%
“…Rossi et al [57] demonstrated how sensitive GPS trajectories are in terms of privacy, while de Montjoye et al [58] proved that even coarsened movement data provide information about individuals. Oksanen et al [59], therefore, proposed a method to preserve privacy in mobility hotspot maps.…”
Section: Data Availability Accessibility and Privacy Concernsmentioning
confidence: 99%
“…The tracking data provided by Sports Tracker (http://www.sports-tracker.com) has previously been used to investigate city dynamics (Ferrari and Mamei 2013) and to create heat maps which enable cyclists to compare potential routes by means of visual data mining (Oksanen et al 2015). The main objective of our study was to extend the aforementioned work by providing the user with automatic popularity-based routing in a street network, by combining recorded workout trajectories with cycling-specific network data extracted from OpenStreet-Map (OSM: openstreetmap.org).…”
Section: The Present Studymentioning
confidence: 99%
“…Mamei (2011, 2013) have used Nokia Sports Tracker application data to identify the areas and temporal routines of a city most used for a given sports activity, highlight cultural and climate-related differences among cities and show differences in the routine behaviour of various demographic and social communities. Oksanen et al (2015) aim to extract frequently used routes from massive public workout data in order to define the most popular routes as a suggestion for application users.…”
Section: Related Researchmentioning
confidence: 99%